The circus - Levez, Olivia (Oneworld Publications, 2017)
Entitled Willow has everything, except a father who really cares about her, so she runs away to find the circus in an attempt to follow in her missing mother's footsteps, but when she winds up homeless and poor instead, all she really needs is a friend to help her.